2008
DOI: 10.2741/2746
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens and progesterone as neuroprotectants: what animal models teach us

Abstract: Estradiol and progesterone are two steroid hormones that target a variety of organ systems, including the heart, the bone and the brain. With respect to the latter, a large volume of basic science studies support the neuroprotective role of estradiol and/or progesterone. In fact, the results of such studies prompted the assessment of these hormones as protective agents against such disorders as Alzheimer's disease, stroke and traumatic brain injury. Interestingly, results from the Women's Health Initiative (WH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 69 publications
3
46
0
Order By: Relevance
“…Therapeutics, such as estrogen (4,34,35), that sustain and enhance mitochondrial functions by up-regulating key regulatory enzymes involved in brain metabolism, efficiency of mitochondrial bioenergetics whereas suppressing oxidative stress could prevent late onset AD.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutics, such as estrogen (4,34,35), that sustain and enhance mitochondrial functions by up-regulating key regulatory enzymes involved in brain metabolism, efficiency of mitochondrial bioenergetics whereas suppressing oxidative stress could prevent late onset AD.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of literature indicates that the ovarian hormones, estrogen (E) and progesterone (P) are neuroprotective (Simpkins et al, 2005, Suzuki et al, 2006, Singh et al, 2008. Animal models have shown that administration of E, prior to or coincident with, trauma or global ischemia decreases tissue damage (McCullough et al, 2001, Hoffman et al, 2006.…”
Section: Introductionmentioning
confidence: 99%
“…strains [106] and the presence of comorbidity [107]. Although very briefl y, estrogen dose (one of the issues addressed in the current thesis) has also been discussed by researchers outside our group [71,101].…”
Section: Estrogens and Cerebral Ischemiamentioning
confidence: 98%
“…For animal studies on the subject, the situation is different. Although the narrative reviews are numerous [67][68][69][70][71], the studies actually utilizing a systematic and/or meta-analytical approach are few. To our knowledge, only three such studies exist: one by Gibson et al from 2006 [72] and two from our lab, Ström et al from 2009 [73], and Paper III of the current thesis.…”
Section: Systematic Reviews and Meta-analyses In Experimental Stroke mentioning
confidence: 99%
See 1 more Smart Citation